2021
DOI: 10.1002/ep.13756
|View full text |Cite
|
Sign up to set email alerts
|

Hydration activity and mechanical properties of steel slag used as cementitious materials

Abstract: The massive steel slag not only occupies land resources but also pollutes the environment, so it is necessary to efficiently utilize steel slag. In this article, the hydration activity and mechanical properties of steel slag used as cementitious materials were studied. Results showed the steel slag was difficult to hydrate at room temperature within 3 days. After the steel slag was autoclaved at 215°C, 2 MPa for 3 h, its hydration degree was 1/3 of that of Portland cement. The expansion rate of the steel slag‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The studies of Wang et al and Zhu et al found new reaction products, C-S-H gel and Ca(OH) 2 , while improving the hydration of steel slag by increasing the temperature and adding NaOH [8] as well as grinding aids [33]. Hou and Liu [34] later improved the hydration by autoclaving and found the same hydration products. However, in these investigations, the hydration products, the overall reactivity, and the hydration reactions were not quantified.…”
Section: Introductionmentioning
confidence: 96%
“…The studies of Wang et al and Zhu et al found new reaction products, C-S-H gel and Ca(OH) 2 , while improving the hydration of steel slag by increasing the temperature and adding NaOH [8] as well as grinding aids [33]. Hou and Liu [34] later improved the hydration by autoclaving and found the same hydration products. However, in these investigations, the hydration products, the overall reactivity, and the hydration reactions were not quantified.…”
Section: Introductionmentioning
confidence: 96%
“…High-density aggregate is obtained by mechanical grinding of rocks containing heavy metals with a density equal to or more than 3000 kg/m 3 . 1 Many types of rocks include heavy metals such as hematite, ilmenite, steel slag (SS), [2][3][4][5] and barite. 6 Concrete with a density higher than 2600 kg/m 3 is HWC.…”
mentioning
confidence: 99%